Experiencias docentes en tiempo de crisis Testimonios desde carreras de Trabajo Social en Chile - Iturrieta, Sandra; Colin, Clément (Ariadna Ediciones, 2023)
In this book we have set out to reconstruct and share the memories of these teaching experiences lived during the pandemic. With this we try to respond to a double need. First, the need not to forget what happened and how it was lived from one's own experiences overflowing with subjectivities. Second, the need to rescue these experiences and remember them, in other words, to make memories to think about the future. In this way, we maintain that the future of teaching and professional work cannot be thought of without taking into account past experiences and, in this sense, those experienced during the pandemic.